Pengembangan Souvenir Berbasis Augmented Reality pada Tempat Wisata Kampung Tridi Malang - Denik Ristya Rini; Ima Kusumawati Hidayat; Dimas Rifqi Novica (Universitas Negeri Malang, 2021)
Abstract: Malang City is the second largest city in East Java Province after Surabaya. The existence of a large city is certainly followed by a dense population. This causes not all residents can live properly. Some of them live in slums in the Watershed (DAS). Facing these problems, the Government of Malang is promoting a program to turn slums into thematic tourist villages. This program is carried out to change the social culture of the community and improve the community's economy. One of the thematic tourist villages in Malang is Kampung Tridi. The village offers a tourism concept with photo spots on a 3D mural wall. Based on observations, Kampung Tridi has been visited by many tourists, but it does not have souvenirs with high selling value. This research intends to develop souvenirs in the form of 3D screen printing t-shirts to improve the local economy. The souvenirs are developed based on the ADDIE (Analysis, Design, Developed, Implementation, Evaluation) development model. The results of the product development are welcomed by the local community as well as tourists. This is seen from the high enthusiasm when this souvenir was launched. Keywords: Tridi village, souvenir, augmented reality Abstrak: Kota Malang merupakan kota terbesar kedua di Provinsi Jawa Timur setelah Kota Surabaya pada urutan pertama. Adanya kota yang besar tentu diikuti dengan danya penduduk yang padat. Hal ini menyebabkan tidak semua penduduk dapat bermukim secara layak. Beberapa diantaranya menghuni perkampungan kumuh di Daerah Aliran Sungai (DAS). Menghadapi permasalahan tersebut pemerintah Kota Malang menggalakkan program mengubah kampung kumuh menjadi kampung wisata tematik. Program ini dilakukan untuk mengubah sosial budaya masyarakat dan meningkatkan perekonomian masyarakat. Salah satu kampung wisata tematik di Malang adalah kampung Tridi. Kampung Tridi menawarkan konsep wisata dengan spot –spot foto pada dinding mural 3 Dimensi. Berdasarkan observasi Kampung Tridi telah banyak dikunjungi oleh wisatawan, namun Kampung Tridi belum memiliki souvenir yang bernilai jual tinggi. Penelitian ini bermaksud mengembangan souvenir berupa kaos sablon 3 Dimensi untuk meningkatkan perekonomian warga sekitar. Souvenir dikembangan berdasarkan model pengembangan ADDIE (Analysis, Design, Developed, Implementation, Evaluation) model. Hasil dari produk pengembangan disambut baik oleh masyarakat sekita dan juga wisatawan. Hal ini dibuktikan dengan adanya antusiasme yang tinggi pada saat souvenir ini diluncurkan. Kata kunci: kampung Tridi, souvenir, augmented reality